Pengaruh Good Corporate Governance dan Profitabilitas terhadap Nilai Perusahaan - Ratnajunita, Kristi; Setiyono, Taufiq Andre (Jurnal Inovasi Akuntansi (JIA), 2025)
This research aims to empirically test the influence of Good Corporate Governance and Profitability on Company Value (Case Study of Pharmaceutical Companies Listed on the IDX 2019-2023). From the results of the Pharmaceutical Research and Manufactures of America (PhRMA) study, it is known that the availability of new medicines in Indonesia is only 9% of the 460 new medicines launched globally during 2012-2021, showing that the limitations of innovative medicines and medical devices have hampered people's access to the best treatment and found inconsistencies in research results measuring company value. The population in this study were pharmaceutical sub-sector companies registered on the IDX in 2019-2023, the sample method used a purposive sampling method, totaling 50 research samples. Based on the results of data processing carried out with the help of SPSS 27. There is a positive influence of the good corporate governance variable on company value, while there is an insignificant influence of the profitability variable on company value. Good corporate governance and profitability have a positive and significant effect on company value.